Assessment tools for transition readiness in adolescents with inflammatory bowel disease: A scoping review - YaHui Zuo; Mei Li; JinJin Cao; Jianan Wang; Wenqian Cai; Lu Zhang; Meng Li (PLoS ONE, 2025)
Background Assessing the level of transition readiness in adolescents with inflammatory bowel disease is crucial; however, standardized research tools are lacking. This study aimed to map transition readiness assessment tools for adolescents with inflammatory bowel disease and determine their suitability. Methods A literature review following the Arksey and O’Malley scoping review methodology was conducted. By using appropriate key terms, literature on transition readiness assessment tool searches were conducted in the CNKI, WanFang, SinoMed, Pubmed, Cochrane Library, Web of Science, and CINAHL databases, with a reference search. The retrieval period was from the establishment of the databases to January 2024. Results A total of 2561 studies were obtained through a preliminary search, and 5 references were obtained as retrospective references. Finally, 21 studies were selected for this review. In total, 20 transition readiness assessment tools were identified. Qualitative findings were grouped into five thematic areas: descriptive characteristics of reviewed articles, development procedures, design, psychometric properties, and cohort characteristics for validity testing of transition readiness assessment tools. Conclusions The most appropriate way to assess the transition readiness of adolescents with inflammatory bowel disease is to select an assessment tool that is most suitable for individual needs, accompanied by a comprehensive patient evaluation. Despite some flaws in the methodology, TRM is currently the most suitable assessment tool, and more population studies are needed to validate it.